2020
DOI: 10.1186/s12903-020-01150-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of 3D printed dental materials for temporary restorations on fibroblasts

Abstract: Background: Three-dimensional (3D) printing is widely used in the fabrication of dental prostheses; however, the influence of dental materials used for 3D printing on temporary restoration of fibroblasts in tissues is unclear. Thus, the influence of different dental materials on fibroblasts were investigated. Methods: Digital light processing (DLP) type 3D printing was used. Specimens in the control group were fabricated by mixing liquid and powder self-curing resin restoration materials. The temporary resin m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…As mentioned above, the DC did not differ significantly between the 60 and 80 • C groups despite the cytotoxicity being lower in the latter group, and significant differences in cytotoxicity were found between all postcuring temperatures. Park et al investigated the influence of different dental resin materials on fibroblasts, and found that 3D printed resin specimens showed better biocompatibility than self-cured resin specimens [43]. The production of 3D printed resin does not involve a chemical reaction, and so there is likely to be less cytotoxicity, whereas self-curing technology does involve chemical reactions [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the DC did not differ significantly between the 60 and 80 • C groups despite the cytotoxicity being lower in the latter group, and significant differences in cytotoxicity were found between all postcuring temperatures. Park et al investigated the influence of different dental resin materials on fibroblasts, and found that 3D printed resin specimens showed better biocompatibility than self-cured resin specimens [43]. The production of 3D printed resin does not involve a chemical reaction, and so there is likely to be less cytotoxicity, whereas self-curing technology does involve chemical reactions [43].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al investigated the influence of different dental resin materials on fibroblasts, and found that 3D printed resin specimens showed better biocompatibility than self-cured resin specimens [43]. The production of 3D printed resin does not involve a chemical reaction, and so there is likely to be less cytotoxicity, whereas self-curing technology does involve chemical reactions [43].…”
Section: Discussionmentioning
confidence: 99%
“…Dental literature includes relevant studies regarding the biocompatibility of the materials used for manufacturing interim prosthetic restorations, with a general focus on the interaction between these materials and oral cells (fibroblasts, epithelial cells, or dental pulp cells); the monomer release; or biofilm formation [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Few studies are dedicated to the influence exercised by interim prosthetic materials on the salivary redox status or inflammatory salivary status.…”
Section: Discussionmentioning
confidence: 99%
“…Souza et al (2020) [ 38 ] also demonstrated that the CAD/CAM acrylic resin was the most compatible with the oral epithelial cells in comparison with the conventional acrylic and bis-acrylic resins. Park et al (2020) [ 39 ] recommended the resins obtained by additive manufacturing for fabricating interim prosthetic restorations over using the auto-polymerized acrylic resins, based on the comparative evaluation of their cytotoxicity (cellular attachment and cell proliferation of mice gingival fibroblasts). Campaner et al (2020) [ 40 ] concluded that the CAD/CAM obtained resins could be considered the most suitable materials for fabricating interim restorations; in this study, the tested auto-polymerized acrylic resin (Alike, Reliance Dental Mfg Co., Worth, IL, USA) and bis-acrylic resin (VIPI Cor, VIPI Industries, Toledo, Spain) induced the greatest adverse effects on mice gingival fibroblasts while the CAD/CAM nano ceramic resin (LAVA Ultimate 3 M ESPE Dental Products, St. Paul’s, MN, USA) and the prefabricated polymer block (Telio CAD, Ivoclar Vivadent AG, Schaan, Liechtenstein) were the most cytocompatible materials and induced the lowest production of IL-6, IL-1β, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Although producing precise temporary restorative materials through 3D printing is critical, there have been a lack of studies regarding its accuracy. Few studies have been performed on 3D-printed temporary restorations, including the cytocompatibility of 3D-printed temporary restorations [ 8 ] and fabrication of highly viscous temporary crowns with fast building speed [ 9 ]. In addition, comparisons on the products of DLP and LCD-type printers have hardly been made.…”
Section: Introductionmentioning
confidence: 99%